2005
DOI: 10.1111/j.1600-0633.2005.00109.x
|View full text |Cite
|
Sign up to set email alerts
|

Foraging behaviour and invasiveness: do invasive Gambusia exhibit higher feeding rates and broader diets than their noninvasive relatives?

Abstract: Foraging behaviour and invasiveness: do invasive Gambusia exhibit higher feeding rates and broader diets than their noninvasive relatives?Un resumen en españ ol se incluye detrás del texto principal de este artículo.Abstract -Serious impacts by nonindigenous species often occur via predation. The magnitude of impact is expected to be closely tied to the invading species niche breadth. For predatory impacts, diet breadth should be particularly important. We examined the relationship between a species foraging b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
70
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 91 publications
(74 citation statements)
references
References 64 publications
4
70
0
Order By: Relevance
“…Whilst many studies ensure that prey are not totally depleted during experiments by supplying the prey in excess (e.g. Rehage et al 2005;Veiga et al 2011), functional response types can still not be revealed by such studies because, with only one prey density examined, the shape of the curve is not known. Thus, impacts on prey populations in terms of the functional response type are not discernible from 'snapshot' study designs.…”
Section: A Comparative Functional Response Framework For Invasion Ecomentioning
confidence: 99%
“…Whilst many studies ensure that prey are not totally depleted during experiments by supplying the prey in excess (e.g. Rehage et al 2005;Veiga et al 2011), functional response types can still not be revealed by such studies because, with only one prey density examined, the shape of the curve is not known. Thus, impacts on prey populations in terms of the functional response type are not discernible from 'snapshot' study designs.…”
Section: A Comparative Functional Response Framework For Invasion Ecomentioning
confidence: 99%
“…Available evidence suggests that the most successful fish invaders appear to be piscivorous or omnivorous and ecological generalists (Kolar & Lodge 2001, Unmack & Fagan 2004. Such predation strategies likely aid invasive species during establishment in novel environments where the food base may differ from the species' natural range (Grabowska & Grabowski 2005, Pine et al 2005, providing an abundance of diverse potential prey resources that would only rarely be limiting (Grabowska & Grabowski 2005, Rehage et al 2005. The generalist feeding strategy that we have documented for Pterois volitans indicates one potential mechanism for the success of this invasive piscivore.…”
mentioning
confidence: 98%
“…Identifying conditions that allow a successful invasion therefore represents a crucial research area. One approach has been to identify characteristics that predispose a species to becoming a successful invader (Kolar & Lodge 2001;Marchetti et al 2004;Rehage et al 2005a). Because invasion is a multi-stage process (introduction, spread, establishment, growth to high density and high impact on an invaded community; Lodge 1993), different characteristics probably affect a species's ability to complete each transition successfully.…”
Section: Introductionmentioning
confidence: 99%